Relationship between corporate culture and psychological safety of training and educational space for young female athletes - Kalenchuk , Valentyna Oleksandrivna; Fedchuk , Oleksandr Valeriyovych; Mykhaylyuk , Vitalii Pavlovich (Insight: the psychological dimensions of society, 2023)
The purpose is to establish correlations between the ideas of young female athletes about corporate culture and psychological safety of training and educational space. The empirical research involved young female athletes (aged 15-17 years; M=16.12; SD=3.11), who trained and studied at a higher school of physical culture (Group I) (n=28; 60.87%) and representatives of this school who continued their sporting and educational-professional career at a higher educational institution (aged 18-21 years; M=19.56; SD=4.05), at the faculties of physical culture and sport and the faculty of psychology, history and sociology (Group II) (n=18; 39.13%). The sample consisted of young athletes who went in for such sports as: handball, volleyball and field and track. Methods: we applied valid methods tested in the sporting area of methodology which allowed determining three types of corporate culture and psychological content parameters of safety of training and educational space. The empirical data are presented through descriptive frequency characteristics. Statistical reliability coefficients – α-Cronbach, Spearman’s correlation (rs), Students’s t-test were used. Results. Different structures of the types of corporate culture of sports educational institutions were created and significant differences of a closed type (CT) (t=-2.42; р<.05) and an open type (OT) (t=2.48; р<.05) were found. It was established that an open type of corporate culture dominates in the respondents’ ideas: Group I (t=2.48; р<.05), Group II (t=2.17; р<.05). Correlations of ОТ with the content parameters of psychological safety were established. It was found out that such correlations are significant for young female athletes: a possibility to demonstrate initiative and activeness (rs=.283; p<.01), maintaining personal dignity (rs=.273; p<.01), a possibility to express their opinions (rs=.173; p<.05), respectful attitude (rs=.163; p<.05), emotional comfort (rs=.143; p<.05), relationships with trainers and teachers (rs=.133; p<.05), assistance in making their decisions (rs=-.113; p<.05), taking into consideration their personal problems and difficulties (rs=-.093; p<.05). The study substantiates that ОТ of corporate culture is desirable for young athletes since they can demonstrate initiative and activeness, maintain personal dignity, satisfy their demand for safe training and educational space, develop thoroughly and fulfill themselves as individuals in its dimensions. Conclusions. The obtained scientific facts should be operationalized into training and educational space of sports educational institutions.